THE IMPACT OF BODY MASS INDEX TO ACUTE MYOCARDIAL INFARCTION IN-HOSPITAL PATIENTS MORTALITY RATE IN DR. KARIADI HOSPITAL - Indra Adhim Karunia Aji; Andreas Arie Setiawan; Ariosta Ariosta; Setyo Gundi Pramudo (DIPONEGORO MEDICAL JOURNAL (JURNAL KEDOKTERAN DIPONEGORO), 2020)
Introduction. Populations with high BMI are at risk for cardiovascular disease because these populations usually have high levels of fat in the body. In contrast, there are several studies that prove that body weight below normal BMI also increases cardiovascular disease risk and death. The aim of this study was to determine the impact of BMI on mortality rates of in-hospital patients with acute myocardial infarction at dr. Kariadi Hospital. Methods. This research is a retrospective analytic observational study with cross sectional design. The sample of this study was acute myocardial infarction patients who were undergoing treatment at the RSUP dr. Kariadi between January 2013 - December 2018 complete data on body weight, height, and status of death or survival. Data comparisons were made using fisher exact test with statistical significant p value was less than 0.05. Results. Statistical analysis using fisher exact test showed association between body mass index and mortality rate is not significant (p = 0,258). Age is the only one confounding variable that showed significant association with mortality rate (p =0,032). Relative risk of age is 1.8 with a cutoff at 60 years. Conclusions. Body mass index (BMI) did not have a significant impact on the mortality rate of AMI in-hospital patients at dr. Kariadi Hospital.Keywords: body mass index, acute myocardial infarction, mortality